2021
DOI: 10.7717/peerj.10600
|View full text |Cite
|
Sign up to set email alerts
|

Liver cancer mortality over six decades in an epidemic area: what we have learned

Abstract: Background and aims: Liver cancer is one of the most dominant malignant tumors in the world. The trends of liver cancer mortality over the past six decades have been tracked in the epidemic region of Qidong, China. Using epidemiological tools, we explore the dynamic changes in age-standardized rates to characterize important aspects of liver cancer etiology and prevention. Methods Mortality data of liver cancer in Qidong from 1958 to 1971 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The incidence of liver cancer in my country has been increasing at an annual rate of over 10% in the past 20 years, and it has become one of the most common clinical malignancies [ 27 ]. In recent years, the expertise and advantages of professional nursing in the prevention and treatment of liver cancer have attracted worldwide attention, especially in improving symptoms, improving the quality of life, and prolonging survival [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of liver cancer in my country has been increasing at an annual rate of over 10% in the past 20 years, and it has become one of the most common clinical malignancies [ 27 ]. In recent years, the expertise and advantages of professional nursing in the prevention and treatment of liver cancer have attracted worldwide attention, especially in improving symptoms, improving the quality of life, and prolonging survival [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 and Figure 3 demonstrate that there were significant differences in the survival rates among age groups, with better prognosis at age of 55-64, poor results at aged over 75. Joinpoint Regression shows that the trends of 5-year RS for each age group were increased markedly, but not for the younger aged at 15-24 (Figure 4), since the most younger patients were occurred in the early period 17 when the survival rates were lower as Table 1 showed.…”
Section: Discussionmentioning
confidence: 96%
“…We have reported that the crude mortality rate of liver cancer in this area had experienced trends from lower to higher levels, and from continued increase at a high plateau to most recently a gradual decline. 17 We believe that many years of comprehensive prevention and intervention measures must have not only influenced the decline of the liver cancer incidence/mortality, but also the survival of the liver cancer patients from the population of this area. Table 1 has showed that the 5-year observed survival (OS) and relative survival (RS) rates during the early calendar years were poor, but improved during the recent years (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary liver cancer, which is widely regarded as one of the most common malignancies all around the world, and its prevalence and mortality are increasing with each passing day [1][2] . Moreover, deaths of liver cancer accounted for 30.53% of all cancer deaths from 1972 to 2017 [3] . At present, the medical treatment of HCC, such as surgical resection [4] , radio-frequency ablation [5] , and liver transplantation can achieve best therapeutic effects [6][7] , but the therapeutic effect and prognosis of HCC are still not optimistic.…”
Section: Introductionmentioning
confidence: 99%